In situ detection of progesterone binding sites in the plasma membrane of the filamentous fungus Rhizopus nigricans - Jeraj, Nataša (Acta chimica slovenica, 2003)
Steroid hydroxylating enzymes in the fungus Rhizopus nigricans are induced by progesterone and by some other steroids. It is known that in higher organisms steroids exert their nongenomic action via steroid binding proteins located inthe plasma membrane of the cells, thus our aim was to detect progesterone binding sites in R. nigricans plasma membrane. In this report membrane receptors were identified by two independent methods, analysis of progesteronebinding to plasma membrane fraction by competitive binding assay using š3Hđ- and š1Hđ progesterone (ECSO=55 nM) and in situ binding of fluorescein isothiocyanate-coupled cell impermeant progesterone conjugate to fungal protoplasts, detected by fluorescence microscopy.
Keywords: Beljakovine, vezava; Binding Sites; Binding, Competitive; Celična membrana; Cell Membrane; Fluorescein-5-Isothiocyanate; Fluorescein-5-izotiocianat; glive; Mesta vezave; Microscopy, Fluorescence; Mikroskopija fluorescenčna; Progesteron; Progesterone; Protein Binding; Protoplasti; Protoplasts; Radioligand Assay; Radioligandi, preiskava; Receptorji progesteronski; Receptors, Progesterone; Rhizopus; Rhizopus nigricans; Vezava kompetitivna; vezna mesta